Leadership and Social Transformation: The Role of Marginalized Individuals and Groups. (25th March 2018) - Rast, David E.; Hogg, Michael A.; Randsley de Moura, Georgina
Abstract: Leadership is a process of influence, an omnipresent feature of human societies, and an enduring focus of research and popular interest. Research tends to focus on individual and situational factors facilitating effective leadership and identifying obstacles to leadership. One key obstacle many leaders face it being stigmatized as an outsider who is not suited to leadership. This article and issue of the Journal of Social Issues focuses on how and when people can overcome these obstacles to leadership–the emergence of marginalized, deviant, or minority group members as leaders even when their success is unexpected. This article and issue discuss the challenges these leaders face and identifies conditions under which such leaders can exert influence to achieve social change. We cover various forms of marginal leadership, focusing on leaders who are marginal individuals (e.g., non‐prototypical leaders), who belong to marginal minority subgroups (e.g., leaders from numerical minority groups), or who have marginal demographic status (e.g., female leaders). This article introduces and frames the subsequent articles in this issue of the Journal of Social Issues, on the psychology of being a marginal leader.